Nitric oxide plays a critical role in methotrexate-induced hyperplasia of enterochromaffin cells containing 5-hydroxytryptamine in rat small intestine - Yuho Takano; Megumi Hirano; Takuji Machida; Yusuke Obara; Naoya Hamaue; Kana Fujita; Masafumi Taniguchi; Tomoko Endo; Saki Shiga; Maiko Machida; Kenji Iizuka; Masahiko Hirafuji (Journal of Pharmacological Sciences, 2019)
The role of nitric oxide (NO) in the changes in enterochromaffin cells and ileal 5-hydroxytryptamine (5-HT) content induced by a single i.p. administration of methotrexate was investigated in rats. Methotrexate significantly increased inducible NO synthase (iNOS) mRNA and protein expressions in the intestinal tissue at 96 h. Methotrexate also significantly caused hyperplasia of the enterochromaffin cells at 96 h; this was associated with a significant increase in 5-HT content. The methotrexate-induced hyperplasia of enterochromaffin cells and increase in 5-HT content were, however, completely suppressed by daily treatment with dexamethasone, and with NG-nitro-l-arginine methyl ester (l-NAME); this was not observed when meloxicam was administered. Histological examination showed slight but not pronounced mucosal injury, at 96 h after methotrexate administration. The methotrexate-induced decrease in body weight did not fully recover to the control level up to 96 h; however, the methotrexate-induced decrease in food/water intake slightly returned to the control level up to 96 h. l-NAME had no significant effect on methotrexate-induced body weight loss and anorexia. To conclude, the present study suggests that NO derived from methotrexate-induced iNOS plays a critical role in the mechanism of hyperplasia of enterochromaffin cells containing 5-HT in the intestinal tissue of rats. Keywords: Methotrexate, 5-Hydroxytryptamine, Enterochromaffin cells, Nitric oxide, Inducible nitric oxide synthase